Actions and structure - "Fielding, Nigel G.(ed.)" (New Delhi, 1988)
Social scientists have always recognised a divergence between approaches which emphasise the constraining power of social structure and those which interpret society through the cumulative effects of actions of individuals. In recent years there has been renewed interest in the latter through the micro-sociology of everyday life. Social scientists are now taking stock of the implications of micro-sociological research for the analysis of structure and the macro-level theory of society. In Actions and Structure the value of micro-sociological research for the analysis of social order is assessed. Individual chapters evaluate new research approaches from discourse and conversational analysis, mathematical, interactionist and phenomenological sociologies and network analysis. Throughout the authors assess how these approaches contribute to current debates around theoretical formulations of organization, structure and power.
Keywords: Methodology